INTEROPERABILITAS QRIS BANK SYARIAH DAN IMPLIKASINYA TERHADAP KEPERCAYAAN SERTA KEPATUHAN SYARIAH PADA UMKM DI KOTA PEKANBARU - Avilla Veronica; Diany Mairiza (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to analyze the interoperability of QRIS issued by Islamic banks and its implications for trust and Sharia compliance among MSMEs actors in Pekanbaru City. This research employs a qualitative descriptive approach using a case study method. The data sources consist of MSMEs actors who use QRIS from Islamic banks and Islamic banking institutions involved in the implementation of digital payment systems. The findings indicate that the interoperability of QRIS issued by Islamic banks has not been optimally integrated, as reflected in delays in payment settlement processes, lack of synchronization between service providers’ systems, and failures in cross-platform transactions. This condition reveals a gap between system design and its practical integration during implementation. The issue is not limited to technical aspects but also affects the level of trust among MSMEs actors toward Islamic digital payment systems, leading to shifts in user behavior toward alternative payment methods perceived as more reliable. From the perspective of Islamic economics, the study finds that the integration of interoperability processes poses potential risks to sharia compliance due to the presence of elements of gharar (uncertainty) in transactions. This may undermine key principles such as the protection of wealth (hifz al-mal), justice (‘adl), and trustworthiness (amanah).